3D In Vitro Neuron on a Chip for Probing Calcium Mechanostimulation. Issue 10 (2nd September 2020) - Bobo, Justin; Garg, Akash; Venkatraman, Prahatha; Puthenveedu, Manoj; LeDuc, Philip R.
Abstract: The evolution of tissue on a chip systems holds promise for mimicking the response of biological functionality of physiological systems. One important direction for tissue on a chip approaches are neuron‐based systems that could mimic neurological responses and lessen the need for in vivo experimentation. For neural research, more attention has been devoted recently to understanding mechanics due to issues in areas such as traumatic brain injury (TBI) and pain, among others. To begin to address these areas, a 3D Nerve Integrated Tissue on a Chip (NITC) approach combined with a Mechanical Excitation Testbed (MET) System is developed to impose external mechanical stimulation toward more realistic physiological environments. PC12 cells differentiated with nerve growth factor, which were cultured in a controlled 3D scaffolds, are used. The cells are labeled in a 3D NITC system with Fluo‐4‐AM to examine their calcium response under mechanical stimulation synchronized with image capture. Understanding the neural responses to mechanical stimulation beyond 2D systems is very important for neurological studies and future personalized strategies. This work will have implications in a diversity of areas including tissue‐on‐a‐chip systems, biomaterials, and neuromechanics. Abstract : Developing more physiologically relevant 3D neuron integrated systems with external mechanics with synchronized image capture enables understanding of cellular responses that are important for advancing future neural studies and personalized strategies. This work examines calcium response with respect to voice coil actuator controlled force profiles.